Enhanced surveillance for tick-borne rickettsiosis and ehrlichiosis in North Carolina: Protocol and preliminary results - Lauryn Ursery; Odai Mansour; Haley Abernathy; Emily Wichmann; Allie Yackley; Alexis Siegler; Dana Giandomenico; Carl Williams; Alexis Barbarin; Michael H. Reiskind; Ross M. Boyce (PLoS ONE, 2025)
North Carolina (NC) experiences some of the highest incidence rates of spotted fever rickettsiosis (SFR) and ehrlichiosis in the United States (US). Due to the non-specific nature of clinical symptoms, minimal utilization of molecular methods when appropriate, and limitations of sero-diagnostic methods, accurate case identification and subsequent public health reporting is challenging. Herein we detail the protocol and early enrollment results for an enhanced surveillance project aiming to generate more accurate estimates of tick-borne disease incidence in NC. Secondary outcomes of interest include: (i) increasing the obtainment rate of convalescent samples (ii) defining demographic and socioeconomic, behavioral/knowledge, entomologic, and environmental risk factors for disease, and (iii) describing the spectrum and clinical course of disease among cases of SFR and ehrlichiosis up to 90 days after symptom onset. In addition, we will collect remnant serum to establish a biorepository of well characterized samples that we intend to make available to researchers. Of the 150 participants enrolled, highlighted results include 49.5% of participants reported being exposed in their own home compared to 43.2% being exposed due to work or travel showing the importance of tick control and education. We also reported more confirmed cases of SFR and ehrlichiosis (15 and 20 respectively) where the North Carolina State Health Department only reported 14 and 11 confirmed cases in the entire state in 2022. Findings from the project will be reported in subsequent publications.